2016
DOI: 10.1162/jocn_a_00919
|View full text |Cite
|
Sign up to set email alerts
|

Are Face and Object Recognition Independent? A Neurocomputational Modeling Exploration

Abstract: Abstract■ Are face and object recognition abilities independent?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…A softmax gating layer is imposed to modulate the learned weights from the hidden layer to the output layer based on the relative contributions of the two modules: if one module is better at processing a given pattern, the gating layer will direct more information (error feedback) through the node corresponding to that module by increasing the value of that gating node. TM has been used to model and explain many cognitive processes, such as the development of hemispheric lateralization in face processing (Dailey & Cottrell, 1999;Wang & Cottrell, 2013), and why the FFA is recruited for non-face categories of expertise (Tong, Joyce, & Cottrell, 2008;Wang, Gauthier, & Cottrell, 2016).…”
Section: The Deep Model (Tdm)mentioning
confidence: 99%
See 1 more Smart Citation
“…A softmax gating layer is imposed to modulate the learned weights from the hidden layer to the output layer based on the relative contributions of the two modules: if one module is better at processing a given pattern, the gating layer will direct more information (error feedback) through the node corresponding to that module by increasing the value of that gating node. TM has been used to model and explain many cognitive processes, such as the development of hemispheric lateralization in face processing (Dailey & Cottrell, 1999;Wang & Cottrell, 2013), and why the FFA is recruited for non-face categories of expertise (Tong, Joyce, & Cottrell, 2008;Wang, Gauthier, & Cottrell, 2016).…”
Section: The Deep Model (Tdm)mentioning
confidence: 99%
“…This analysis of the hidden layer activation has proved useful in the past: In work explaining why the FFA is recruited for new object categories of expertise, Tong et al (2008) showed that fine-level discrimination leads to an expanded representational space that also spreads out new stimuli, while basic level categorization "clumps" objects in representational space, making it difficult to distinguish individual members of a category. In work modeling the effect of experience in face and object recognition, Wang et al (2016) demonstrated that more experience results in more separation in the hidden unit representational space, and that helps recognize objects of expertise. In this work, we used this technique to analyze the difference between central and peripheral representations generated in TDM.…”
Section: Now That We Know Peripheral Vision Contains Better Features mentioning
confidence: 99%
“…Note, as mentioned above, that these studies will not necessarily lead to strategies for instruction of non-experts, at least not directly. Moreover, when cognitive processes are mostly implicit or too fast to unravel behaviorally, such as in pattern recognition (System 1 reasoning), neuroscience research can tap into the nature of these processes in a more fine grained manner and compare with neurocognitive processes similar to pattern recognition (e.g., object recognition, Wang et al 2016). Note that these fast processes are typically observed in experts, and relate to components of expertise theory, adding to the conclusion that EN research in health sciences education appears to bear most value in relation to expertise-related questions.…”
Section: Convergence Of Evidencementioning
confidence: 99%
“…In childhood and adolescence, however, there are also some functional commonalities in face and object processing that are typically not observed in adulthood (Joseph et al; Jüttner et al). Accordingly, the development of face perception could be understood as a process where domain-general and domain-specific mechanisms dissociate across childhood and adolescence as a result of increasing face-related expertise (e.g., Wang et al, 2016). The development of domain-specific processes can proceed at different rates for different modules of face processing (e.g., Weigelt et al, 2014).…”
Section: Face Perception: Where Development and Aging Meetmentioning
confidence: 99%